2019
DOI: 10.1210/js.2019-00190
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Treatment With Müllerian-Inhibiting Substance Synchronizes Follicles and Enhances Superovulation Yield

Abstract: Müllerian-inhibiting substance (MIS), also known as anti-Müllerian hormone, is thought to be a negative regulator of primordial follicle activation. We have previously reported that treatment with exogenous MIS can induce complete ovarian suppression within 5 weeks of treatment in mice. To investigate the kinetics of the return of folliculogenesis following the reversal of suppression, we treated animals with recombinant human MIS (rhMIS) protein for 40 days in adult female Nu/Nu mice and monitored the recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…AMH plays an important role in several reproductive functions, including Müllerian duct regression and regulation of folliculogenesis. As a result, AMH has been implicated in several reproductive disorders and cancers and is thus a target of interest in therapeutic intervention of these diseases and as a contraceptive agent also capable of protecting ovarian reserve during chemotherapy and enhancing yield during in vitro fertilization (4,6). Furthermore, because AMH is the only ligand which binds AMHR2, this makes AMH and AMHR2 ideal for therapeutic targeting, while limiting potential off target effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMH plays an important role in several reproductive functions, including Müllerian duct regression and regulation of folliculogenesis. As a result, AMH has been implicated in several reproductive disorders and cancers and is thus a target of interest in therapeutic intervention of these diseases and as a contraceptive agent also capable of protecting ovarian reserve during chemotherapy and enhancing yield during in vitro fertilization (4,6). Furthermore, because AMH is the only ligand which binds AMHR2, this makes AMH and AMHR2 ideal for therapeutic targeting, while limiting potential off target effects.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, males are born with normal male reproductive organs but additionally develop a uterus and Fallopian tubes from the remaining portions of the Müllerian duct. More recently, it has been shown that AMH plays a fundamental role in the regulation and progression of follicles within the female ovary (4). Specifically, overexpression of AMH in the ovary can suppress early folliculogenesis (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatally, in females, MIS is mainly produced by granulosa cells of secondary and early antral follicles and acts through its specific receptor, MISR2 (AMHR2), which is expressed in granulosa cells of all types and in ovarian surface epithelium (OSE) (14). MIS produced by growing follicles is thought to provide a negative feedback to prevent primordial follicle activation, a function that has been supported by in vitro and in vivo studies in rodents and humans (15)(16)(17)(18).…”
Section: Significancementioning
confidence: 99%
“…Although AMH protein administration was performed in mice, prolonged systemic treatment (subcutaneous injections every 12 hours for 40 days) resulted in supraphysiologic serum levels of AMH, i.e., $1,000 ng/mL based on pharmacokinetic data for subcutaneous AMH injection in mice, relative to a physiologic level of <50 ng/mL (12)(13)(14)(15). Consequently, follicular development was completely suppressed from the early-growing to antral stage and the estrous cycles ceased (12). A negative correlation was observed between AMH expression, at mRNA and protein levels, in GCs and antral follicle sizes in rats (2) and sheep (16).…”
mentioning
confidence: 99%